2002
DOI: 10.1002/jhet.5570390519
|View full text |Cite
|
Sign up to set email alerts
|

Novel fluorescent quater‐ and quinquifurans: Syntheses and photophysical properties

Abstract: In the quest for fast fluors for use in waveshifting polystyrene fibers, symmetrical oligofurans were investigated. Furan moieties were coupled by means of the Ullmann Reaction or by palladium-catalyzed unsymmetrical coupling; the latter gave higher yields. While the benzoxazole-terminated quater-and quinquifurans we prepared were both stable and fast, exhibiting a green fluorescence and decay times of about 2.4 nsec, they were inferior to other types of fluors in solubility and emission intensity when incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
(49 reference statements)
0
13
0
2
Order By: Relevance
“…The group of Kaufmann was the first to describe the synthesis of 2 F and 4 F using the Ullmann reaction (Scheme 2), [17] and later used a Negishi coupling to yield the substituted 5 F. [18] Ishida et al, used a Stille coupling to synthesize 3 F. [25] Attempts to obtain longer oligofurans resulted in unstable and inseparable mixtures. [26] In 2010, we found that the Stille coupling of a,w-dibromooligofurans with monostannyloligofurans gives long oligofurans (5 F-8 F) in good yields (Scheme 3).…”
Section: Synthesis Of Oligofuransmentioning
confidence: 99%
See 1 more Smart Citation
“…The group of Kaufmann was the first to describe the synthesis of 2 F and 4 F using the Ullmann reaction (Scheme 2), [17] and later used a Negishi coupling to yield the substituted 5 F. [18] Ishida et al, used a Stille coupling to synthesize 3 F. [25] Attempts to obtain longer oligofurans resulted in unstable and inseparable mixtures. [26] In 2010, we found that the Stille coupling of a,w-dibromooligofurans with monostannyloligofurans gives long oligofurans (5 F-8 F) in good yields (Scheme 3).…”
Section: Synthesis Of Oligofuransmentioning
confidence: 99%
“…Short oligofurans up to 4 F were reported about 30 years ago, [17] and only one example of a substituted a-oligofuran consisting of five rings [18] was known prior to the 2010 synthesis of long a-oligofurans (nF). [19][20][21][22] As can be seen in Figure 1, oligofurans have a 0.3-0.4 eV higher HOMO-LUMO gap than oligothiophenes.…”
Section: Introductionmentioning
confidence: 99%
“…Die Gruppe von Kaufmann beschrieb als erste die Synthese von 2 F und 4 F mithilfe der Ullmann‐Reaktion (Schema )17 und setzte später eine Negishi‐Kuppling zur Herstellung des substituierten 5 F ein 18. Ishida et al.…”
Section: Synthese Und Molekulare Eigenschaftenunclassified
“…Kurze Oligofurane bis zu 4 F wurden bereits vor etwa 30 Jahren beschrieben,17 und es war nur ein Beispiel eines substituierten, aus fünf Ringen bestehenden α‐Oligofurans bekannt,18 bevor 2010 die Synthese eines langen α‐Oligofurans n F gelang 1922. Wie aus Abbildung 1 ersichtlich, weisen Oligofurane einen um 0.3–0.4 eV größeren Energieunterschied zwischen dem HOMO und dem LUMO auf als Oligothiophene.…”
Section: Introductionunclassified
“…In addition, oligofurans were regarded as "green" materials, as furan can be directly obtained from renewable bioresources 12 and are easily biodegradable 13 . However, compared to the thio-analog, oligothiophenes (nTs), which were considered among the workhorses in the field of organic electronic materials 14 , nF have been overlooked for a long time [15][16][17][18][19][20][21] . A decade ago, researchers have already demonstrated that oligofurans exhibited higher fluorescence, better solubility, greater rigidity, and tighter solid-state packing than the corresponding nTs.…”
mentioning
confidence: 99%